Continuous recordings of environmental parameters at station 14, Kalkgrund (2022-09 - 2024-10) - Lieberum, Christian; Hiebenthal, Claas; Karez, Rolf (In: Lieberum, C et al. (2024): Time series of environmental parameters of habitats along the Schleswig-Holstein Baltic Sea (2018 et seq) [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.972419, 2026)
Additionally, at four shallow water stations (Booknis Eck, Buelk, Behrensdorf and Katharinenhof) temperature, salinity and dissolved oxygen are continuously logged at 2-3 m depth by self-contained data loggers. These are: (I) MiniDOT loggers (Precision Measurement Engineering; http://pme.com; ±10 µmol L-1 or ±5 % saturation) including copper antifouling option (copper plate and mesh) to measure dissolved oxygen concentration and (II) DST CT salinity & temperature loggers (Star-Oddi; http://star-oddi.com; ±1.5 mS cm-1) to record the conductivity. Both sensor types additionally record water temperature with an accuracy of ± 0.1 °C. The sampling interval was set to 30 minutes for all parameters. In context of the long-term monitoring project RegLocDiv (Regional-Local-Diversity) by M. Wahl (Franz, M. et al. 2019a), another seven stations were equipped with the same two types of sensors at 4-6 m depth to continuously record environmental parameters (again: temperature, salinity, dissolved oxygen) and included into this data set. These stations are at: Falshoeft, Booknis Eck, Schoenberg, Westermarkelsdorf, Staberhuk, Kellenhusen and Salzhaff (abandoned in 2023). Since 2021, in the context of implementing a reef monitoring to fulfil obligations by the EU Habitats Directive, step-by-step, eleven further stations were installed at reefs in the Schleswig-Holstein Baltic Sea. These are at: Platengrund (14 m depth) and Mittelgrund (8 m) (both since 2021), at Walkyriengrund (9 m), Brodtener Ufer (8 m), Außenschlei (11 m), Kalkgrund (8 m), Stollergrund (7.5 m) and Flueggesand (10 m) (all since 2022), as well as at Gabelsflach (10 m), Sagasbank (8.5 m) and Stabehuk (11.5 m) (all since 2023). Again, at all of these 11 stations, temperature, salinity and dissolved oxygen are continuously logged by self-contained data loggers: Conductivity (and temperature) is logged by HOBO® Salt Water Conductivity/Salinity Data Logger (Onset Computer Corporation, Bourne, MA, USA; https://www.onsetcomp.com) using the U2X protective housing to prevent fouling on the sensors. The same MiniDOT loggers (Precision Measurement Engineering) as at the above mentioned more shallow stations (including antifouling copper plate and mesh) are used to measure dissolved oxygen concentration. Dissolved oxygen concentration data measured by the MiniDOT loggers are corrected for a depth of 10 m (or 2,5 m on the shallow stations) using the software provided by the manufacturer. Additionally, a manual compensation for salinity was calculated (see details in Franz, M. et al. 2019b). Quality control was carried out by spike and gradient tests, following recommendations of SeaDataNet quality control procedures (see https://seadatanet.org/Standards/Data-Quality-Control). All data values were flagged according to applied quality checks using the following flags: 1 = Pass, 2 = Suspect, 3 = Fail, 4 = Visually suspect, 5 = Salinity compensation fail (further explanations can be found in Franz, M. et al. 2019b).
Keywords: Baltic Sea; Loggers; Oxygen; Reefs; Salinity; Schleswig-Holstein; shallow-water; Temperature